2008
DOI: 10.1007/s10350-008-9246-z
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Patients with High-Risk Stage II Colon Cancer for Adjuvant Therapy

Abstract: Patients with Stage II colon cancer generally have an excellent prognosis. However, the presence of multiple adverse prognostic factors identifies a high-risk subgroup. Use of commonly reported clinicopathologic features accurately stratifies Stage II colon cancer by disease-specific survival. Those identified as high-risk patients can be considered for adjuvant chemotherapy and/or enrollment in investigational trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
144
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(154 citation statements)
references
References 20 publications
7
144
0
3
Order By: Relevance
“…We believe that our data on p-CEA, along with data from other previously mentioned authors, can help in the stratification of patients with high risk of relapse, even independently from an advanced staging, 5,6,29,44 who can benefit most from both intra-or postoperative adjuvant therapies and tighter controls.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…We believe that our data on p-CEA, along with data from other previously mentioned authors, can help in the stratification of patients with high risk of relapse, even independently from an advanced staging, 5,6,29,44 who can benefit most from both intra-or postoperative adjuvant therapies and tighter controls.…”
Section: Discussionmentioning
confidence: 51%
“…11 These observations, which were made as recently as 2013 and which still seem surprising after 30 years, are certainly not due to the lack of testing new molecular, genetic, or humoral markers, but to the fact that these are not reliable, simple, nor cost effective as the CEA could be. In recent years, we are not the only ones 1,3,4,6,7,10,11,16,18,19,[27][28][29] who believe that the determination of the p-CEA has a prognostic value in identifying, preoperatively, the group of patients who most likely will show recurrences. In fact, p-CEA is able to identify both patients whose understaging results from occult metastasis and those who are carriers of histologically advanced or more aggressive neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, gender, TNM stage, venous invasion, tumour necrosis, peri-tumoural lymphocytic infiltration, tumour budding and CEA levels were also independently associated with poor survival in at least some studies [17,18,21,22,26,30,32,33,39].…”
Section: Discussionmentioning
confidence: 97%
“…12,13 Features that confer high risk of recurrence in stage II colon cancer include large tumors (T4), bowel perforation or obstruction, lymphovascular invasion, poorly differentiated histology, positive margins, or inadequate lymph node sampling. [14][15][16] Guideline recommendations for patients with stage III colorectal cancer are based on high-quality randomized controlled trials that have demonstrated that adjuvant chemotherapy for stage III colon cancer 17-21 and neoadjuvant radiation with or without chemotherapy for stage III rectal cancer [22][23][24][25][26] improve outcomes. Treatment of stage II colon and rectal cancers is more controversial.…”
Section: Introductionmentioning
confidence: 99%